Implementasi Konsep Eco Friendly dan Green Tourism pada Cipta Hotel Pancoran – Jakarta - Alesandra Ephyna; Cherish Olivier; Keisya Shalka; Muhammad Dafidhan; Ramadhania Syabilah; Revalina Sopiyan; Sandy Yudha; Tiara Pakpahan (Penerbit Jurnal Indonesia, 2026)
This study aims to analyze the implementation of zero waste and green tourism concepts at Cipta Hotel Pancoran - Jakarta as part of sustainable hospitality practices. The study uses a qualitative descriptive approach with a case study method. Data were collected through direct observation, interviews with hotel management, and documentation related to environmental management practices. The results indicate that Cipta Hotel Pancoran - Jakarta has implemented various sustainability initiatives, including waste management in collaboration with local environmental authorities, reduction of single-use plastic through refillable amenities, energy and water efficiency policies, and environmental awareness programs for staff and guests. Although some initiatives such as eco-enzyme and organic waste processing faced operational challenges, these efforts demonstrate the hotel’s commitment to continuous improvement in supporting environmental sustainability and green tourism development.